Saudi Arabia : 2016 Article IV Consultation-Press Release; Staff Report; and Informational Annex. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2016)
Saudi Arabia has begun a fundamental policy shift to respond to low oil prices. The government has introduced a series of reforms over the past year and has recently set out plans for a bold and ambitious transformation of the Saudi Arabian economy in Vision 2030 and the National Transformation Program. Diversifying the economy, creating jobs for nationals in the private sector, and implementing a gradual, but sizable and sustained fiscal consolidation are key policy priorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet